Combustion behaviors and temperature characteristics in pulverized biomass dust explosions. (July 2018) - Jiang, Haipeng; Bi, Mingshu; Li, Bei; Gan, Bo; Gao, Wei
Abstract: Flame propagation behaviors and temperature characteristics of four types of biomass with two different particle size distributions were studied experimentally. Results show that the flame front of a 50–70 μm biomass is nearly spherical and smooth, the flame zone is characterized by yellow or dark red spotted flames, and luminous flames are present behind it. The flame morphology of 100–200 μm biomass dust is irregular and discrete. The average flame propagation velocity and the amplitude of the velocity fluctuation are functions of the mass density of the biomass particles and depend on the particle size distributions. The flame-speed oscillation of biomass particles is caused by the velocity slip between the volatile gases and particles. Flame temperatures of 50–70 μm and 100–200 μm biomass dust reach the maximum value at 1000 g/m 3, and show a slight dependence on the particle size distribution. An analysis of the Knudsen number indicates that the combustion characteristics of biomass particles with particle size distributions within the range studied are characterized by a continuum regime. It is indicated that 100–200 μm poplar sawdust will be the "best" option as a biomass replacement feedstock for coal powered plants. Highlights: Flame configurations in pulverized biomass dust explosions was observed. Pulsating flame propagation in biomass dust clouds was observed. The flame temperature increased proportionally with particle size. The combustion characteristics of biomass dust were marked by a continuum regime.